Participation but not success in youth and junior World Championships is important for overall ranking in the biathlon World Cup during adult age - Jonsson Kårström, Malin (Frontiers in Sports and Active Living, 2024)
The aim of this study was to investigate if competition rank in the youth (16-19 years) and junior (20-22 years) World Championships (WCH) and age of the athlete when reaching certain World Cup (WC) performance milestones (debut and top 40, 15, 6 and 3) were related to future World Cup total (WCT) performance.All data was obtained from the International Biathlon Unions database. The biathletes ranked top 30 in the WCT (82 men, 98 women) during 10 consecutive competition seasons were selected for further analysis.Biathletes were divided into performance groups due to their best WCT ranking (WCT6, rank 1-6; WCT15, rank 7-15; WCT30, rank 16-30). The relation between youth and junior WCH ranking and age when reaching the WC performance milestones with WCT performance was investigated.63.3% and 86.1% of the biathletes in the WCT top 30 competed in the youth and/or junior WCH, respectively, but the correlation between junior and senior ranking was low. WCT6 reached most of the WC performance milestones at a younger age compared to WCT15 and WCT30 (p>0.05) and reaching WC top15 at a younger age increased the chance of reaching WCT6 in the future.It seems beneficial to compete internationally (i.e. participation in youth/junior WCH) and reach certain WC performance milestones at a young age to achieve a high ranking in the WCT during adult age. This highlights that biathletes need to have a certain performance level during junior years, although ranking in youth/junior WCH is not a prediction for senior WCT success.